Pelvic Floor Muscle Exercise (PFME) on Bristol Stool Scale Type - Veroneka Yosefpa Windahandayani; Lilik Pranata; Aniska Indah Fari; Keristina Ajul (Sarana Ilmu Indonesia (salnesia), 2023)
The elderly is an increasingly old age, characterized by changes and decreased ability to function in the body, one of which is gastrointestinal function, the problem that is often encountered is defecation control. The aim of the study was to see differences in stool scales based on the bristol stool scale before and after pelvic floor muscle exercise (PFME) in the elderly. The method in this study was quantitative with a pre-experimental design pre-post one group without control, on 21 research subjects who were selected by purposive sampling technique. The research data were analyzed using the Wilcoxon rank test. The results of the descriptive data study showed that pre-intervention constipation was 57,0%, ideal stool 28,6%, diarrhea 14,3%, after-intervention constipation 23.80%, ideal stool 66,66, diarrhea 9,5%, and test results different from the p-value <0,05, namely = 0,009, meaning that there is an effect on the stool scale before and after being given the PFME intervention. Researchers provide recommendations for the elderly to do Pelvic Floor Muscle Exercises in daily and scheduled activities.